Assessing Service Quality of Bike Sharing Service within Kathmandu Valley - Chaudhary, Ambika; Kumar Shrestha, Pradeep; Shrestha, Saurav (International Journal on Engineering Technology, 2024)
Embracing a sustainable transportation paradigm requires a shift towards more eco –friendly modes of travel such as bike sharing services like Pathao & Indrive, Introducing a potentially disruptive and beneficial change to the transportation landscape in Nepal, bike-sharing hold a significant presence in Kathmandu, evidenced by their daily ridership and public recognition. Being a comparatively new concept, its service assessment becomes critical for the persistence of the facility. Perceived service quality assessment is a result of convoluted decision making process which require careful considerations of various factors including observed and unobserved variables. The study focuses on evaluating the service quality of Pathao & Indrive bike service employing the concept of structural equation modeling through the identification of unobserved influencing factors. Six latent variables were identified through factor analysis. An empirical model was developed to identify the interactions among major variables affecting service quality. SPSS 22 and SPSS Amos 21 were used for model development. The findings of the study presented that, the variable that have significant effect on service quality, was user’s safety followed by latent variables service accessibility & application efficiency. The study will provide practical insights to these services to enhance their effectiveness and usability making the service more acceptable. It will also provide clarity in understanding to inform adoption of suitable policy decisions.